2, 4, 6‐Tri(hydroxy)‐1, 3, 5‐triphosphinine, P3C3(OH)3: The Phosphorus Analogue of Cyanuric Acid. Issue 5 (27th December 2016) - Suter, Riccardo; Mei, Yanbo; Baker, Matthew; Benkő, Zoltan; Li, Zhongshu; Grützmacher, Hansjörg
Abstract: Cyanuric acid (C3 H3 N3 O3 ) is widely used as cross‐linker in basic polymers (often in combination with other crosslinking agents like melamine) but also finds application in more sophisticated materials such as in supramolecular assemblies and molecular sheets. The unknown phosphorus analogue of cyanuric acid, P3 C3 (OH)3, may become an equally useful building block for phosphorus‐based polymers or materials which have unique properties.1 Herein we describe a straightforward synthesis of 2, 4, 6‐tri(hydroxy)‐1, 3, 5‐triphosphinine and its derivatives P3 C3 (OR)3 which have been applied as strong π‐acceptor η 6 ‐ligands in piano stool Mo(CO)3 complexes. Abstract : Done in three ticks : The trimerization of boryl‐substituted phosphaalkynes allows the straightforward synthesis of triphosphabenzenes on a multi‐gram scale. These compounds give stable metal complexes and can be further functionalized at the oxygen centers.